Potency of Eucalyptus Oil and Citronella Oil in Suppressing Virulence Factors of Xanthomonas oryzae pv. oryzae: Potensi Minyak Kayu Putih dan Minyak Serai Dapur dalam Menekan Faktor Virulensi Bakteri Xanthomonas oryzae pv. oryzae - Alifia Nur Ayusma; Widiastuti, Ani; Triwidodo Arwiyanto (Jurnal Fitopatologi Indonesia, 2024)
Bacterial leaf blight, caused by the bacterium Xanthomonas oryzae pv. oryzae (Xoo), is an important disease of rice and can cause yield losses of 10-50%. Efforts to control bacterial leaf blight in rice using eucalyptus oil and citronella oil have not been widely reported. This study aims to evaluate the potential inhibition of eucalyptus oil and citronella oil against X. oryzae pv. oryzae isolate code BaK_2 in vitro, focusing on X. oryzae pv. oryzae virulence factors. The virulence factor assay consisted of biofilm formation, exopolysaccharide (EPS) production and motility. The results showed that eucalyptus oil and citronella oil could inhibit the growth of X. oryzae pv. oryzae in vitro. The minimum inhibitory concentration (MIC) was 15% for eucalyptus oil and 5% for citronella oil. Virulence factor tests showed that eucalyptus oil and citronella oil had no significant effect on biofilm formation, but could reduce EPS formation and limit the movement of X. oryzae pv. oryzae by both swimming motility and motility.